Crude malva nut gum affects pasting and textural properties of wheat flour in the presence or absence of sodium chloride - Phimolsiripol Y. (2014)
This research aims to investigate the effect of crude malva nut gum (CMG) addition on pasting and textural properties of wheat flour in the presence or absence of sodium chloride (NaCl). The mixtures were prepared by adding 0, 2.5, 5, 7.5 and 10% of CMG into wheat flour. Pasting results revealed that addition of CMG significantly elevated (P≤0.05) the peak viscosity (126-676 RVU), hot paste viscosity (75-333 RVU), breakdown (50-342 RVU) and final viscosity (153-552 RVU). Pasting temperature (61-83°C) of the pastes decreased with increasing CMG content. The textural parameters including hardness, springiness, cohesiveness, gumminess and chewiness of the mix gels decreased with addition of CMG. The presence of 0.75% NaCl in the mixtures had higher viscosity than the presence of 0 and 1.5% NaCl in the mixtures. The hardness of gel mixed with 0-2.5% CMG increased with increasing NaCl levels, while no significant effect (P>0.05) at higher level of CMG (7.5- 10%). Higher paste viscosity and softer gel texture of wheat flour could be altered using CMG. The presence of NaCl affects both pasting and textural properties in different ways.